Leverage, Ownership Concentration and Organisational Characteristics: Determinants of Green Accounting Disclosure in Indonesia - Ni Kadek Githa Prastya Putri; Luh Gede Krisna Dewi (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
Green accounting disclosure represents a mechanism through which firms demonstrate accountability to stakeholders on matters pertaining to sustainability. This study investigates the influence of leverage, ownership concentration, and firm-specific characteristics on the extent of green accounting disclosure. The analysis is underpinned by agency theory and stakeholder theory. The empirical context of this research is the manufacturing sector listed on the Indonesia Stock Exchange (IDX) over the 2020–2023 period. The study employs a purposive sampling approach, yielding a sample of 175 firms and 398 firm-year observations. Data analysis is conducted using the Random Effects Model (REM) framework, facilitated by STATA 17 statistical software. The findings indicate that firm characteristics are positively associated with green accounting disclosure. In contrast, the analysis reveals no statistically significant relationship between leverage or ownership concentration and green accounting disclosure. Kata Kunci: Pengungkapan Green Accounting; Leverage; Konsentrasi Kepemilikan; Karakteristik Perusahaan